BAS/BSCR12 Proteomic analysis of smooth muscle cells derived from carotid plaque shows differences between symptomatic and asymptomatic plaques. Issue 17 (26th August 2010) - Full, L E; Davies, A H; Wait, R; Monaco, C
Abstract : Rationale: Smooth muscle cells (SMC) are key players in atherosclerotic disease. The proteome of SMC in human carotid disease and its relationship with plaque-related symptomatology are still ill defined. Methodology: Carotid endarterectomy specimens were collected from 10 consenting patients (six symptomatic, four asymptomatic). Plaque SMC were isolated via enzymatic dissociation of endarterectomy specimens and using immunomagnetic beads (Miltenyi). Commercially available aortic medial SMC from six healthy donors were purchased from Promocell. Cells were used consistently at passage 3. We used two-dimensional electrophoresis with digital image analysis (SameSpots, Non-linear Dynamics) and tandem mass spectrometry to detect changes in proteome of atherosclerotic SMC. Results: Analysis of 2D gel images revealed 29 proteins with a statistically significant difference in expression between medial and plaque SMC (p<0.05). Plaque SMC had decreased expression of mitochondrial protein ATP synthase subunit β but an increase in the oxidised form of peroxiredoxin-4, suggesting decreased mitochondrial function, possibly owing to oxidative stress. Glycolytic enzyme pyruvate kinase was also increased by 50% in plaque SMC. Furthermore, differences in protein expression between SMC from symptomatic and asymptomatic patients were also found. Plaque SMC from symptomatic patients exhibited increased expression of heat shock protein-60 and decreased levels of the anti-inflammatory protein annexin I (p<0.05), compatible with a proinflammatory behaviour. These findings were confirmed by immunoblotting. Conclusions: Our data demonstrate that plaque-derived SMC are exposed to higher levels of oxidative stress than control SMC. Differences between SMC from symptomatic and asymptomatic patients appear to reflect proinflammatory changes associated with plaque instability.